Assessing Liquidity Buffers in the Panamanian Banking Sector - Komaromi, Andras (IMF Working Papers; Working Paper ;, 2016)
This paper assesses the resilience of Panamanian banks to (i) a very severe short-term, and (ii) a significant long-lasting liquidity shock scenario. Short-term liquidity buffers are evaluated by approximating the Liquidity Coverage Ratio (LCR) defined in the Basel III accord. The risk of losing a substantial part of foreign funding is analyzed through a conventional liquidity stress test scrutinizing several layers of liquidity across maturity buckets. The results of this study point to some vulnerabilities. First, our approximations indicate that about half of Panamanian banks would need to adjust their liquid asset portfolios to meet current LCR standards. Second, while most banks would be able to meet funding outflows in the stress-test scenario, a number of banks would have to use up all of their liquidity buffers, and a few even face a final shortfall. Nonetheless, most banks displaying sizable liquidity shortfalls have robust solvency positions.